PREDICTIVE ANALYTICS IN CLINICAL DATA AND PATIENT OUTCOMES - Prem Kumar Tamanam, (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2025)
Predictive analytics has emerged as a transformative force in modern healthcare, revolutionizing how medical institutions leverage clinical data and deliver patient care. This comprehensive article examines the implementation, applications, benefits, and challenges of predictive analytics in healthcare settings. The article explores the impact of data analytics training programs on healthcare professionals' performance, the role of electronic health records in improving operational efficiency, and the applications of machine learning algorithms in disease detection and treatment planning. The article investigates the benefits of predictive analytics in clinical decision-making, preventive care, personalized medicine, and cost optimization while addressing critical challenges related to data quality, ethical considerations, and workflow integration. Through analysis of multiple healthcare institutions and extensive patient data, this study demonstrates the substantial potential of predictive analytics to enhance healthcare delivery while highlighting important considerations for successful implementation.